The development of a model for dealing with secondary traumatic stress in mental health workers in Rwanda - Jean D. Iyamuremye; Petra Brysiewicz (AOSIS, 2015)
Introduction: Mental health workers who listen to stories of fear, pain and distress of traumatised clients may develop deleterious emotional, cognitive and physical consequences (Cairns, 2007). This phenomenon has been called secondary traumatic stress (STS) (Perez, Jones, Englert, & Sachau, 2010). Rwanda is well-known for the 1994 genocide, with the death of hundreds of thousands of people in a planned campaign of violence. Numerous mental health workers operating in Rwanda were also victims of the violence and it has been suggested that there is a high level of STS in mental health workers in Rwanda (Iyamuremye & Brysiewicz, 2008). Aim: To develop a comprehensive model to manage the effects of STS in mental health workers operating in Rwanda. Method: An action research project was initiated to develop this model and data for the model was collected through individual interviews with mental health workers (nurses, doctors, psychologists, trauma counsellors and social workers) as well as a quantitative tool measuring secondary traumatic stress (Trauma Attachment Belief Scale) in these health workers. Results: The Intervention Model to Manage Secondary Traumatic Stress (IMMSTS) was synthesised from these findings and includes preventive, evaluative and curative strategies to manage STS in mental health workers in Rwanda at the individual, social and organisational levels. Conclusion: The model will offer mental health professionals an effective framework for addressing the issue of STS.